Application of Intermittent Fasting to Changes in Blood Sugar Levels in Type 2 Diabetes Mellitus Patients - Hanny Irmaya; Yuli Yanti; Tiara Vionika (Indonesian Journal of Global Health Research, 2023)
Type 2 DM is a metabolic disorder caused by a lack of insulin hormone. (Intermittent Fasting) is an effective method used to help lower and stabilize blood glucose in patients with Type II Diabetes Mellitus. This type of research is a description with a case study approach model. The sample is 2 respondents with Type II Diabetes Mellitus. The application of intermittent fasting diet to respondents with type 2 diabetes mellitus obtained different results, where the first respondent was unsuccessful in carrying out the intermittent fasting diet marked by the GDS levels before and after the intervention were still the same, namely 225 mg / dl, while the second respondent had results marked by GDS before the intermittent fasting diet was 220 mg / dl and after the intermittent fasting diet became 202 mg / dl. Conclusion of the intermittent fasting diet can be seen whether or not there is compliance in carrying out intermittent fasting to determine stable blood sugar levels. In the first respondent, there was no effectiveness because they did not comply with the existing rules in carrying out the intermittent fasting diet which resulted in no decrease in blood sugar levels, while for the second respondent there was a decrease in blood sugar levels and had effectiveness in the intermittent fasting diet, if both respondents did it optimally it would cause a decrease in blood sugar levels.